Study on Mechanism of Influence of Mining Speed on Roof Movement Based on Microseismic Monitoring - Ke Ma; Su-jian Wang; Fu-zhen Yuan; Yi-lin Peng; Shi-min Jia (Advances in Civil Engineering)
Based on the study of the movement rule of the rock strata under the influence of the mining speed in the typical working face of Dongjiahe coal mine, the distribution of microseismic events and the variation characteristics of microseismic parameters in the slow and fast advancing stage are compared and analyzed, and the mechanism of the rock strata activity under the influence of the mining advancing speed is revealed from the perspective of the microfracture. The results show that the movement of the roof strata and the stress adjustment of surrounding rock have certain timeliness. The maximum advanced distance of microseismic events in the slow and fast stages is 185 m and 130 m, respectively, and the maximum lag distance of microseismic events in the goaf is 120 m and 180 m, respectively. The time of stress adjustment of surrounding rock is short, and the load transfer of the roof is insufficient. The advanced distance of microseismic events is increased, and the lag distance decreases. The percentage of microseismic events in the total number of events is 47% and 38%, respectively, in the slow and fast stages of advancing. With the increase of mining speed, the intensity of roof strata activity in the goaf is weakened. The rock failure decreases and the volume of broken block increases, and roof collapse and rotary subsidence are insufficient. During the nonpressure period, the maximum development elevation of microseismic events is +350 m and +300 m, respectively, in the slow and fast stages, while with the development elevation of microseismic events in the roof pressure near +390 m, increasing the mining speed cannot change the final failure height of the overburden. During the analysis period of roof pressure, the concentrated release of microseismic energy in the faster stage is 183% of that in the slower stage. The increase of large moment magnitude event frequency leads to the decrease of b value. The risk of roof instability and strata behavior increases.